OLD-CZECH, OLD-SLAVIC, AND OLD-CHURCH-SLAVIC - ON THE SEMANTIC FIELDS OF THREE ADJECTIVES - David, Jaroslav (Bohemica Olomucensia, 2020)
The goal of the study is to examine the semantics of adjectives staročeský [old-Czech], staroslovanský [old-Slavic], and staroslověnský [old-Church-Slavic]. The analysis is based on their collocations in the Czech National Corpus data, specifically in the synchronic written corpus SYN, version 8; there, their appearances are compared in the fiction, academic, and opinion journalism subcorpora. The adjectives are used in two basic meanings - they refer to the linguistic-literary facts and to the cultural-historical ones. The adjectives staroslovanský and staroslověnský, regarding the world of Old Slavs and the old-Church-Slavic language, are the most semantically transparent. In case of the adjective staročeský, a reference to the events, cuisine, and food is the striking feature, mostly in opinion-journalism texts; it reflects the usage of the adjective in marketing texts with a semantic shift to 'having a good quality, traditional'.
Keywords: collocation analysis; corpus; old-Czech; old-Slavic; old-Church-Slavic; personal names